Designing for human use: Examples of kitchen interiors for persons with disability and elderly people. Issue 2 (17th October 2018) - Bonenberg, Agata; Branowski, Bogdan; Kurczewski, Przemysław; Lewandowska, Anna; Sydor, Maciej; Torzyński, Dariusz; Zabłocki, Marek
Abstract: Around 15% of the global population has a moderate or severe disability. For this reason, a design where the needs of elderly and disabled population are included, should become more common practise and should not be limited only to medical and rehabilitation products. In this study, the inclusive design practices related to the kitchens were applied. All the important stages in a design process, such as market research, planning, concept designing, detailed designing, research (ergonomic assessment), and production preparation were completed. In market research we market research examined the preferences of 216 respondents. Sixty percent of them were either elderly and/or disabled persons (direct users), 40% were caretakers, physiotherapists, and managers of care centres (indirect users). Implementation of obtained results is three kitchen lines with assistive technology solutions, which are the response to the requirements identified as appropriate in meeting the needs of the elderly and disabled kitchen users. The main conclusion of the article is the statement that the needs of seniors can and should be efficiently included in a design process of home interiors. It can be recognised as an important "social" designing criterion which can constitute a good basis for going beyond the traditional design and going toward the sustainable design.